Xiaoyaosan Ameliorates Chronic Immobilization Stress-Induced Depression-Like Behaviors and Anorexia in Rats: The Role of the Nesfatin-1–Oxytocin–Proopiomelanocortin Neural Pathway in the Hypothalamus - Ma, Qingyu; Li, Xiaojuan; Yan, Zhiyi; Jiao, Haiyan; Wang, Tingye; Hou, Yajing; Jiang, Youming; Liu, Yueyun; Chen, Jiaxu (Frontiers in Psychiatry, 2019)
Background: Chronic stress is an important risk factor for depression. The nesfatin-1 (NES1)-oxytocin (OT)-proopiomelanocortin (POMC) neural pathway, which is involved in the stress response, was recently shown to have an anorectic effect in the hypothalamus. Our previous study showed that Xiaoyaosan, a well-known antidepressant used in traditional Chinese medicine (TCM), effectively relieved appetite loss induced by chronic immobilization stress (CIS). However, whether Xiaoyaosan ameliorates depression-like behaviours and anorexia by regulating the NES1-OT-POMC neural pathway remains unclear. Objective: To investigate whether the antidepressant-like and anti-anorexia effects of Xiaoyaosan are related to the NES1-OT-POMC neural pathway in the hypothalamus. Methods: Rats were randomly divided into control, CIS, Xiaoyaosan treatment, and fluoxetine treatment groups. The rats in the CIS, Xiaoyaosan treatment and fluoxetine treatment groups were subjected to CIS for 21 consecutive days, during which they were administered distilled water, a Xiaoyaosan decoction [3.854 g/(kg·d)] or fluoxetine [1.76 mg/(kg·d)], respectively, by gavage, and their body weights and food intake were monitored daily. The rats were subsequently subjected to the open field test (OFT) and sucrose preference test (SPT). Then, the expression levels of corticosterone and NES1 in the serum and the expression levels of NES1, OT, POMC, and melanocortin-4 receptor (MC4R) in the hypothalamus were determined by real-time fluorescence quantitative polymerase chain reaction (RT-qPCR), Western blot analysis and immunochemistry. Furthermore, immunofluorescence double staining was used to determine whether related proteins in the hypothalamic NES1-OT-POMC neural pathway were co-expressed. Results: Compared to control rats, rats exposed to CIS exhibited gradually less food intake and lower body weights and significantly increased concentrations of NES1 in the serum and paraventricular nucleus (PVN). Moreover, the expression levels of POMC, OT and MC4R in the hypothalamus were significantly higher in the CIS group than those in the control group. However, these changes were reversed by pretreatment with Xiaoyaosan and fluoxetine. Specifically, the expression levels of members of the NES1-OT-POMC neural pathway were lower in the Xiaoyaosan-treated group than in the CIS group. Conclusion: Xiaoyaosan ameliorates CIS-induced depression-like behaviours and anorexia by regulating the NES1-OT-POMC neural pathway in the hypothalamus.